Design of a Wi-Fi based electrocardiography monitoring system - Kocatürk, Mehmet. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2007., 2007)
The objective of this project is to design a wireless ECG monitoring system which enables the tracking of ambulatory patients' cardiac activities on a central server. A developed software run on a server and the client devices on patients yield providing support for nearly real-time traceability of patient ECG data. The software on the server, which is technically able to handle unlimited numbers of connections of client devices, appropriately communicates with the remote devices and provides plotting of electrocardiogram of a selected patient who is preregistered with the software. The client device, carried by the patient, includes an ECG ampli er circuit which also includes necessary lters to avoid undesired signals, and manages analog to digital conversion of ampli ed ECG signal as well as its transmission to the server. IEEE 802.11b, as the wireless communication protocol, opted and involved in this design for ensuring data transmission between client devices on patients and the server, has rapidly penetrated in applications in Machine to Machine (M2M) communicating product lines except medical ones. What is more, due to rapid penetration of 802.11x (Wi-Fi) which simpli es the adaptation of the client devices developed with this study to the currently established networks, the designed system, in the aim of wireless ECG monitoring, can be foreseen to supply high e ciency in the further products of several ECG monitoring applications.|Keywords: ECG, Wi-Fi, IEEE 802.11, Telemedicine.
Keywords: Electrocardiography.; IEEE 802.11 (Standard)